2022
DOI: 10.2217/fmb-2022-0053
|View full text |Cite
|
Sign up to set email alerts
|

Combined Antibiofilm Activity of Synthetic Peptides and Antifungal Drugs Against Candida Spp.

Abstract: Introduction: Candida krusei and Candida albicans are biofilm-forming drug-resistant yeasts that cause bloodstream infections that can lead to death. Materials & methods: nystatin and itraconazole were combined with two synthetic peptides, PepGAT and PepKAA, to evaluate the synergistic effect against Candida biofilms. Additionally, scanning electron and fluorescence microscopies were employed to understand the mechanism behind the synergistic activity. Results: Peptides enhanced the action of drugs to inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…As reported in many other studies from our research group, synthetic peptides are not toxic to human red blood cells (HRBC) [10,12]. Additionally, it has been shown that during synergistic action, peptides, besides enhancing drugs' effects, also reduce their toxicity to HRBC [11,13].…”
Section: Hemolytic Actionsupporting
confidence: 61%
See 2 more Smart Citations
“…As reported in many other studies from our research group, synthetic peptides are not toxic to human red blood cells (HRBC) [10,12]. Additionally, it has been shown that during synergistic action, peptides, besides enhancing drugs' effects, also reduce their toxicity to HRBC [11,13].…”
Section: Hemolytic Actionsupporting
confidence: 61%
“…The ROS overproduction was determined following the method described by Bezerra et al [13]. The assays were conducted as the same for PI analysis.…”
Section: Overproduction Of Reactive Oxygen Species (Ros)mentioning
confidence: 99%
See 1 more Smart Citation
“…These include the use antimicrobial peptides, inhibitors of other components within the biofilm matrix ( i.e . extracellular DNA), the use of probiotics, hsp90 inhibition, as well as modulators of quorum sensing [ [87] , [88] , [89] , [90] , [91] , [92] , [93] ]. An interesting methodology being developed and applied to the Candida biofilm field is that of photodynamic therapy (PDT), where the inhibitory activity is mediated by the action of reactive oxygen species generated by the photoactivation of a photosensitizer by a light source [ [94] , [95] , [96] , [97] ].…”
Section: The Futurementioning
confidence: 99%
“…When developing biomimetics and some combinations with them, special attention is paid to minimizing their toxicity (or its complete absence) in relation to human/animal/plant cells, as well as to the type of antifungal effect (mechanism of action) on cells in order to avoid the development of resistance [76,145]. At the initial stage of such investigations, toxicity is assessed using modern computer modeling methods [146].…”
Section: Combination Of Antifungal Peptides With Each Other And/or Wi...mentioning
confidence: 99%

Various Biomimetics as Antifungals

Efremenko,
Aslanli,
Stepanov
et al. 2023
Preprint